2020
DOI: 10.1111/ctr.14079
|View full text |Cite
|
Sign up to set email alerts
|

Acute heart failure after liver transplantation: A narrative review

Abstract: Acute heart failure (AHF) is present in a substantial proportion of patients after liver transplantation (LT), and is associated with significant morbidity and mortality. 1-4 The pretransplant hemodynamic changes (decreased systemic vascular resistance (SVR), poor ventricular response to stress and increased cardiac output) that occur in patients with end-stage liver disease (ESLD) coupled with the effects of pro-inflammatory cytokines released during reperfusion of the liver during transplantation have been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 105 publications
(216 reference statements)
0
7
0
Order By: Relevance
“…Although the majority of the aforementioned risk factors are nonmodifiable, their presence should trigger active surveillance for acute HF so that treatment can be instituted as early as possible. 7,14…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the majority of the aforementioned risk factors are nonmodifiable, their presence should trigger active surveillance for acute HF so that treatment can be instituted as early as possible. 7,14…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of the aforementioned risk factors are nonmodifiable, their presence should trigger active surveillance for acute HF so that treatment can be instituted as early as possible. 7,14 This study is limited by its retrospective single-center nature, which is based on an electronic review of medical records. The decision to perform echocardiography was based on clinical judgment; hence, not all patients underwent echocardiography during the first 12 mo after LT.…”
Section: Postoperative Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Corinna Oschatz et al (2022) found that the presence of an example increases the engagement of the audience with the narrative, which indirectly has a positive effect on the attitude and behavior of the audience. Sharma et al (2020) also studied 118 media students at the Western University of…”
Section: Narrative Persuasion and Interpersonal Talkmentioning
confidence: 99%